Rancang Bangun Pagar Otomatis dengan Finger Print Berbasis Mikrokontroller - Usman Usman; Abdul Abdul Azis Rahmansyah; Nur Fajri Apriadi (P3M Politeknik Negeri Indramayu, 2017)
The fence is one of the leading security in maintaining a building. Conventional fence require operator to open and close it, so it does not effective and efficient. This problem can be solved with automated systems. This research aims to design fance system using finger print sensor based microcontroller arduino, which is equipped with a locking system that use a solenoid. This experimental research is starts from the design, fabrication and testing. Fences made have specifications 3.2 m x 1.5 m with a total weight is 30.67 kg, path lengthis 2.1 m, diameter sprocket 0.03 m, Voltage DC motor is 12 V and rotation is 195 rpm. The test results showed a good performance conform with its initial design, where a fence can be opened with a fingerprint has been recorded before. Solenoid can open and lock, likewise with the the photodiode can detect object is on the track. The test results obtained there are differences when opening / closing compared with the results design is 20%, with an average voltage is 12.06 V, current is 1 A, rotation is 135 rpm, and the time it takes 9.9 s, where the torque produced is of 0.64 Nm and maximum load can be driven by a DC motor is at 59.97 kg.